2022
DOI: 10.3390/plants12010101
|View full text |Cite
|
Sign up to set email alerts
|

Water Deficit-Induced Changes in Phenolic Acid Content in Maize Leaves Is Associated with Altered Expression of Cinnamate 4-Hydroxylase and p-Coumaric Acid 3-Hydroxylase

Abstract: The amino acid phenylalanine is a precursor to phenolic acids that constitute the lignin biosynthetic pathway. Although there is evidence of a role of some phenolic acids in plant responses to pathogens and salinity, characterization of the involvement of phenolic acids in plant responses to drought is limited. Drought reduces water content in plant tissue and can lead to decreased cell viability and increased cell death. We thus subjected maize seedlings to water deficit and evaluated relative water content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These reports contradicted the results observed both in our study and another preceding study [ 43 ] on stressed Medicago sativa L., where a decreased abundance of PAL was correlated with elevated levels of cinnamic acid. Our recent assessment of the maize response to water deficit suggested that drought leads to altered levels of phenolic acids, driven by changes in the expression of genes encoding cinnamate 4-hydroxylase and p-coumaric acid 3-hydroxylase [ 44 ]. Thus, assessing the levels of phenolic acids and flavonoids in sorghum and maize will contribute to the understanding of how enzymes in the phenylpropanoid biosynthesis pathway influence the responses to drought in these two C4 plant species.…”
Section: Discussionmentioning
confidence: 99%
“…These reports contradicted the results observed both in our study and another preceding study [ 43 ] on stressed Medicago sativa L., where a decreased abundance of PAL was correlated with elevated levels of cinnamic acid. Our recent assessment of the maize response to water deficit suggested that drought leads to altered levels of phenolic acids, driven by changes in the expression of genes encoding cinnamate 4-hydroxylase and p-coumaric acid 3-hydroxylase [ 44 ]. Thus, assessing the levels of phenolic acids and flavonoids in sorghum and maize will contribute to the understanding of how enzymes in the phenylpropanoid biosynthesis pathway influence the responses to drought in these two C4 plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study examined the content of both HBAs (gallic acid and syringic acid) and HCAs (ferulic acid, caffeic acid, p -coumaric acid, and chlorogenic acid) available in drought-stressed maize inbred lines under different NP treatments ( Figure 7 ). According to Kolo et al [ 87 ], drought stress caused a 0.3-fold decrease of p -coumaric acid in maize leaf, whereas caffeic acid and ferulic acid in leaf increased by 0.9-fold and 0.3-fold, respectively. Further, Rayee et al [ 88 ] examined 13 standard phenolic acids in MNR2 and Koshihikari rice varieties under chilling stress.…”
Section: Discussionmentioning
confidence: 99%